2019
DOI: 10.1101/770693
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased cell size, structural complexity and migration of cancer cells acquiring fibroblast organelles by cell-projection pumping

Abstract: We recently described a hydrodynamic mechanism for cytoplasmic transfer between cells, termed cell-projection pumping (CPP). Earlier image analysis related altered SAOS-2 osteosarcoma cell morphology, to what we now recognize as CPP uptake of fibroblast cytoplasm. We here examine SAOS-2 phenotype following co-culture with human dermal fibroblasts (HDF) in which organelles were pre-labelled with a fluorescent lipophilic marker. Fluorescence activated cell sorting (FACS) analysis was performed of HDF and SAOS-2,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 32 publications
4
16
2
Order By: Relevance
“…One limitation of those earlier reports, was that we only studied cell phenotype in co-culture, and not cells separated after co-culture according to the extent of CPP uptake (1,18). This is addressed in more recent work submitted elsewhere but available as a pre-print (34), in which we study MC sub-populations separated by fluorescence activated cell sorting on basis of the level of fibroblast label uptake. We found that acceptance of fibroblast marker increased MC migration and cell size (34).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One limitation of those earlier reports, was that we only studied cell phenotype in co-culture, and not cells separated after co-culture according to the extent of CPP uptake (1,18). This is addressed in more recent work submitted elsewhere but available as a pre-print (34), in which we study MC sub-populations separated by fluorescence activated cell sorting on basis of the level of fibroblast label uptake. We found that acceptance of fibroblast marker increased MC migration and cell size (34).…”
Section: Discussionmentioning
confidence: 99%
“…This is addressed in more recent work submitted elsewhere but available as a pre-print (34), in which we study MC sub-populations separated by fluorescence activated cell sorting on basis of the level of fibroblast label uptake. We found that acceptance of fibroblast marker increased MC migration and cell size (34). Internal complexity was also increased, as Simulations predicting fluorescence profiles for recipient cells similar to experimental results ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations